Pengenalan Hasil Tambang Bumi di Indonesia Menggunakan Augmented Reality Sebagai Alat Bantu Edukasi - Yuliantoro, Achmad, Hernawan Sulistyanto, S.T., M.T (2016)
Mine is the result of natural resources that cannot be renewed. Indonesia is one of the countries which has overflowing pruducts of mining, including coal, gold, silver, bauxite, copper, nickel, sulphur and marble. The overflowing products of mining countries, including Indonesia, need for an interesting learning media. It is pointed to make younger generation has an interest to know and learn the products of mining in Indonesia. Augmented Reality technology can be used as learning media. One of uses is by designing and building educational applications by applying the technology of Augmented Reality on android-based mobile application with SDLC (System Development Life Cycle) method. The building of the application needs the Unity3D software and Vuforia SDK to build the Augmented Reality, and Blender software to build 3-Dimensional objects. In the application is also put exercises to develope users' knowledge tounderstand the material of products of mining in Indonesia. The result of research was tested to the third year of elementary school students in Sekolah Dasar 3 Plesungan, Karanganyar. The test of the application was by giving a demonstration to the students and letting the students to operate the application . Based on data from the questionnaire, the application can attract and help students in learning the products of mining in Indonesia. There are two results from the test; 1). 81% of the students stated the main menu of the application is clear and interesting. 2). 87% of the students stated this application was able to increase their desire to study. More of the results shows there is a developement of students' grade after the application was applied.